Discrimination of millipedes by the opossum Didelphis albiventris (Marsupiala, Didelphidae) - Santori, Ricardo T. [UNESP] (My University, 1998)
Millipedes are toxic preys for many vertebrates. Two individuals of the opossum species D. albiventris were videorecorded when feeding on the millipedes G. olivaceus and L. dentellus. Data were compared with feeding behavior on Tenebrio larvae. The opossums are resistant to intoxication by millipedes. Although chemical defenses of the millipedes were not effective against the opossum predation, they make them less attractive.